Fully Human Monoclonal Antibody Inhibitors of the Neonatal Fc Receptor Reduce Circulating IgG in Non-Human Primates - Nixon, Andrew E.; Chen, Jie; Sexton, Daniel J.; Muruganandam, Arumugam; Bitonti, Alan J.; Dumont, Jennifer; Viswanathan, Malini; Martik, Diana; Wassaf, Dina; Mezo, Adam; Wood, Clive R.; Biedenkapp, Joseph C.; et al. (Frontiers in Immunology, 2015)
The therapeutic management of antibody-mediated autoimmune disease typically involves immunosuppressant and immunomodulatory strategies. However, perturbing the fundamental role of the neonatal Fc receptor (FcRn) in salvaging IgG from lysosomal degradation provides a novel approach – depleting the body of pathogenic immunoglobulin by preventing IgG binding to FcRn and thereby increasing the rate of IgG catabolism. Herein, we describe the discovery and preclinical evaluation of fully human monoclonal IgG antibody inhibitors of FcRn. Using phage display, we identified several potent inhibitors of human-FcRn in which binding to FcRn is pH-independent, with over 1000-fold higher affinity for human-FcRn than human IgG-Fc at pH 7.4. FcRn antagonism in vivo using a human-FcRn knock-in transgenic mouse model caused enhanced catabolism of exogenously administered human IgG. In non-human primates, we observed reductions in endogenous circulating IgG of >60% with no changes in albumin, IgM, or IgA. FcRn antagonism did not disrupt the ability of non-human primates to mount IgM/IgG primary and secondary immune responses. Interestingly, the therapeutic anti-FcRn antibodies had a short serum half-life but caused a prolonged reduction in IgG levels. This may be explained by the high affinity of the antibodies to FcRn at both acidic and neutral pH. These results provide important preclinical proof of concept data in support of FcRn antagonism as a novel approach to the treatment of antibody-mediated autoimmune diseases.